2021
DOI: 10.3390/microorganisms9091984
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Mosaic Disease: Characteristics, Identification and Control

Abstract: Mosaic is one of the most important sugarcane diseases, caused by single or compound infection of Sugarcane mosaic virus (SCMV), Sorghum mosaic virus (SrMV), and/or Sugarcane streak mosaic virus (SCSMV). The compound infection of mosaic has become increasingly serious in the last few years. The disease directly affects the photosynthesis and growth of sugarcane, leading to a significant decrease in cane yield and sucrose content, and thus serious economic losses. This review covers four aspects of sugarcane mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 118 publications
0
32
0
1
Order By: Relevance
“…Sugarcane ( Saccharum officinarum L.) is the world’s most crucial sugar and energy crop ( Lu et al, 2021 ; Tayyab et al, 2021 ), and it is mainly cultivated in tropical and subtropical climates with an annual production of about 16 million tons worldwide ( Chandel et al, 2012 ; Khalil et al, 2018 ). However, studies have established that cane growth and development are known to absorb a significant amount of soil nutrients because it produces large amounts of biomass ( Oliveira et al, 2018 ; Camargo and Keeping, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane ( Saccharum officinarum L.) is the world’s most crucial sugar and energy crop ( Lu et al, 2021 ; Tayyab et al, 2021 ), and it is mainly cultivated in tropical and subtropical climates with an annual production of about 16 million tons worldwide ( Chandel et al, 2012 ; Khalil et al, 2018 ). However, studies have established that cane growth and development are known to absorb a significant amount of soil nutrients because it produces large amounts of biomass ( Oliveira et al, 2018 ; Camargo and Keeping, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Basnayake et al reported that drought had reduced sugarcane production by up to 60% [ 10 ]. Mosaic, one of the main viral sugarcane diseases, has resulted in stunted plants, reduced photosynthesis, destruction of chlorophyll and inhibition of plant growth and which can ultimately reduce sugarcane yield by 10–50%, or even 60–80% [ 11 , 12 ]. Approximately 1300 insect pests have been accounted for attacking sugarcane around the world, and stem borer is the most harmful pest in most countries, resulting in yield losses of nearly 25–30% [ 1 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane diseases caused by SrMV infection are widely distributed worldwide, and rice diseases caused by RSMV infection are becoming more serious and spreading year by year (Yang et al, 2018;Lu et al, 2021). Rapid and accurate detection of these viruses is helpful for forecasting and preventing the epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…Sorghum mosaic virus (SrMV), genus Potyvirus, family Potyviridae, is one of the main pathogens causing sugarcane mosaic disease, and is widely distributed in major sugarcane regions in the world at present (Lu et al, 2021). The rapid detection and identification of this virus is helpful to control the sugarcane mosaic disease in the field.…”
Section: Introductionmentioning
confidence: 99%